2022
DOI: 10.1536/ihj.22-207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrical Muscle Stimulation on the Reduction of Muscle Volume Loss in Acute Heart Failure Patients

Abstract: Electrical muscle stimulation (EMS) is expected to be considered as an add-on therapy for the usual rehabilitation of patients with chronic heart failure (HF). However, it remains unclear whether EMS can reduce muscle volume loss in patients with acute HF (AHF) immediately after hospitalization. Therefore, the aim of this study was to investigate if EMS could reduce the lower-limb muscle volume loss in patients with AHF. In this single-center, retrospective, observational study, lower-limb skeletal muscle volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…One non-controlled cohort study of 10 weeks ( 14 ) and a further non-randomized clinical trial of 4 months ( 38 ) included solely participants with chronic heart failure ( 14 , 38 ). Matsuo et al ( 23 ) and Tanaka et al ( 36 ) selected acute heart failure as an eligibility criterion and applied 10 and 14 days of B-SES during hospitalization in their moderate quality studies. In parallel, about 50% of the critically ill patients of Nakamura et al ( 25 , 26 ) and 70% of the hemodialysis patients included in the moderate quality RCT of Homma et al ( 16 ) reported heart failure, cardiopulmonary arrest or had a history of ischemic heart disease ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One non-controlled cohort study of 10 weeks ( 14 ) and a further non-randomized clinical trial of 4 months ( 38 ) included solely participants with chronic heart failure ( 14 , 38 ). Matsuo et al ( 23 ) and Tanaka et al ( 36 ) selected acute heart failure as an eligibility criterion and applied 10 and 14 days of B-SES during hospitalization in their moderate quality studies. In parallel, about 50% of the critically ill patients of Nakamura et al ( 25 , 26 ) and 70% of the hemodialysis patients included in the moderate quality RCT of Homma et al ( 16 ) reported heart failure, cardiopulmonary arrest or had a history of ischemic heart disease ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies included hospitalized cohorts with end-stage diabetes kidney disease ( 37 ) or diabetic ulcers undergoing minor amputation ( 18 ). Additionally, four other trials did not focus on, but included a large proportion of participants with NIDDM ( 16 , 22 , 23 , 34 ). Of importance, a further three moderate to high quality RCTs ( 12 , 20 , 28 ) focused on cohorts with the Metabolic Syndrome (MetS) applying WB-EMS for 3–6 months.…”
Section: Resultsmentioning
confidence: 99%
“…More than two thirds of the studies/projects reported changes body composition parameters as primary, secondary or tertiary outcome. Although difficult to conclude 8 , about 14 studies considered changes in body composition and anthropometry at least as a core outcome [21,23,27,39,44,49,50,53,54,58,59,63,68,77] (Figure 3 31,39,44,57,75,92], one study [37] relied on the caliper method and a further study [53] determined changes in thigh and calf circumference.…”
Section: Body Composition and Anthropometrymentioning
confidence: 99%
“…Apart from total body fat, several studies determined trunk, abdominal, or visceral fat mass/rate by BIA [46,65], DXA [19,31,39,41] or CT [68] or, less sophisticated, by waist circumference [19, 21,39,65,71,75,94]. Eleven studies focus on local muscle parameters (muscle thickness, cross-sectional area, crosssectional volume) predominately at the mid-thigh/quadriceps site [23,27,29,46,54,58,59,63,68,83,86], calf [23] or upper arm [27] applying either ultrasound (US) [23,27,29,63,86], computed tomography (CT) [58,59,68] or magnetic resonance imaging (MRI) [46,83] techniques. Of relevance, five of the studies consider thigh muscle layer thickness (by US) as a primary outcome [23,54,58,59,63].…”
Section: Body Composition and Anthropometrymentioning
confidence: 99%
See 1 more Smart Citation